1988
DOI: 10.1159/000116600
|View full text |Cite
|
Sign up to set email alerts
|

Central Organization of Wave Localization in the Clawed Frog, <i>Xenopus laevis</i>

Abstract: The central nervous organization of water wave localization in the clawed frog Xenopus laevis was investigated by performing behavioral tests on frogs that had various brain ablations. The criterion of localization was the orientation of response turns toward the origin of stimulus waves. After complete midbrain ablation, Xenopus still detected impinging waves but could not localize them. After thalamopretectal ablation, however, Xenopus localized waves with normal accuracy. Thus, wave localization can be acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Potentially at least, some of those units could match by their spatial tuning the behavioural localization accuracy of the animal (5°; Elepfandt, 1982). Behavioural tests after midbrain lesions had suggested that it is mainly the anterior extension of the TM which is involved in stimulus localization and that here wave source directions are represented in a systematic order (Elepfandt, 1988b). In this regard, the prevalence of BF classes £ 25 Hz in the rostral midbrain invites us to consider these frequencies to be vital for wave source localization.…”
Section: Midbrain Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially at least, some of those units could match by their spatial tuning the behavioural localization accuracy of the animal (5°; Elepfandt, 1982). Behavioural tests after midbrain lesions had suggested that it is mainly the anterior extension of the TM which is involved in stimulus localization and that here wave source directions are represented in a systematic order (Elepfandt, 1988b). In this regard, the prevalence of BF classes £ 25 Hz in the rostral midbrain invites us to consider these frequencies to be vital for wave source localization.…”
Section: Midbrain Responsesmentioning
confidence: 99%
“…the torus semicircularis principalis (TP) and magnocellularis (TM; Will et al 1985b;Edwards & Kelley, 2001). Among these nuclei, the TM possibly exhibits divisions concerned with wave source localization and frequency resolution, respectively (Elepfandt, 1988b;Reisbeck, 1994). Notably, substantial projections of the torus semicircularis reach the optic tectum (OT), where lateral line units of remarkable spatial selectivity were observed (Zittlau et al, 1986(Zittlau et al, , 1988compare Claas, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Information of the lateral line is sent to the lateral line nucleus, then to the cerebellum, and the torus semicircularis in the midbrain [14]. Elepfandt [1,15] showed that a partial lesion of the torus semicircularis caused inaccurate orienting responses, suggesting that this area had a topographical map that represented the direction of the water wave. In addition, the optic tectum receives the output from the torus semicircularis and has similar topographic map as the torus semicircularis [13].…”
Section: Brain Areas That May Be Responsible For the Mnemonicmentioning
confidence: 99%
“…African clawed frogs (Xenopus laevis) capture living insects on the water surface by analyzing the directions of water waves produced by the movement of the prey [1]. During this orienting behavior, water waves are predominantly detected by lateral lines that are dispersed over the frog's body.…”
Section: Introductionmentioning
confidence: 99%